The Initiation of Dialysis: As Good as It Gets! - Fragoso,Andre (2014)
The quality of pre-dialysis care of chronic kidney patients has been shown to be associated with the outcome after renal replacement therapy. Referral to the nephrologist should be done on time. The renal care team has the best expertise to prepare patients to start dialysis, treat progression factors and complications of end-stage renal disease. The initiation of dialysis must be prepared and decided previously, and the choice of the dialysis modality discussed with the patients and their families, whenever possible. The establishment of a permanent dialysis access is crucial. The renal function at which patients must start treatment is under discussion. Probably the medical related conditions are more important than the level of renal function itself